2013
DOI: 10.1123/tsp.27.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Mind Over Matter: The Development of the Mental Toughness Scale (MTS)

Abstract: Mental Toughness (MT), which refers to an inner focus and commitment to rise above challenges when facing adversity, is viewed as one of the most important psychological attributes in determining success in sport. However, there is little consensus on key components of MT, and existing measures vary greatly while focusing on elite athletes. The purpose of this research was to develop a measure of MT for use with college athletes. Collegiate and noncollegiate athletes (N = 271) completed the original 54-item Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 37 publications
1
26
0
2
Order By: Relevance
“…However, it appears from our research that this becomes less relevant with increasing age. Bear in mind that our mental toughness factor was comprised of items that extended beyond narrower definitions of this construct (Madrigal, Hamill, & Gill, 2013;Nicholls, Polman, Levy, & Backhouse 2009). Exercise motives that loaded significantly on this factor reflected interest in developing assertiveness, creating opportunities for achievement, building self-esteem, generating new life skills, and becoming mentally tougher.…”
Section: Discussionmentioning
confidence: 99%
“…However, it appears from our research that this becomes less relevant with increasing age. Bear in mind that our mental toughness factor was comprised of items that extended beyond narrower definitions of this construct (Madrigal, Hamill, & Gill, 2013;Nicholls, Polman, Levy, & Backhouse 2009). Exercise motives that loaded significantly on this factor reflected interest in developing assertiveness, creating opportunities for achievement, building self-esteem, generating new life skills, and becoming mentally tougher.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of many of these studies is the use of sport-specific measures to objectively evaluate performance, which, compared to competitive standard, provide more direct evidence supporting the influence of MT on athletic performance. However, given MT applies primarily to the most critical, pressurized, or adversarial competitive situations [11,49], it is surprising that only two studies have measured competitive performance indices of this kind [4,42]. In both studies, there was limited support for the superior performance of mentally tougher athletes during such conditions.…”
Section: Mental Toughness Achievement and Performancementioning
confidence: 99%
“…The seven studies that compared or associated MT with competitive performance indices involved a single sport, and only one (14.3%) did not find that MT predicted performance [42]. One of the remaining six studies found MT was associated with some performance statistics and not others [4], and another found that MT predicted performance for males, but not females [41].…”
Section: Mental Toughness and Competitive Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…As mental toughness is typically measured through self-report scales that are developed from theoretical or sporting-based conceptualisations, it is important for researchers to understand how these tools correspond to participants' ideas of the concept. Second, as the meaning of mental toughness is likely to be contextually bound (Bull et al, 2005;Fawcett, 2011;Madrigal, Hamill, & Gill, 2013), lay theories may highlight previously overlooked components of mental toughness (Harasymchuk & Fehr, 2013). Finally, understanding lay perceptions of mental toughness may contribute to promoting further recognition and understanding of the benefits that can be attained by mental toughness beyond sporting and achievement-related contexts.…”
Section: [In Order Of Importance]mentioning
confidence: 99%